2006
DOI: 10.1007/bf03031815
|View full text |Cite
|
Sign up to set email alerts
|

Trends in intercountry adoption: Analysis of data from 20 receiving countries, 1998–2004

Abstract: The implications of developments in intercountry adoption worldwide in the early years of the twenty-first century are explored, based on analysis of data from 20 receiving countries. Between 1998 and 2004, intercountry adoption increased by 42 per cent. Problems in data collection and analysis are examined, as is the reliability of estimates of numbers of children sent by countries of origin when derived from data provided by receiving countries. Also considered are various measures of standardization which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 13 publications
(32 reference statements)
1
60
0
4
Order By: Relevance
“…With respect to this trend, UNICEF (1999) has estimated the number of international adoptions to seven major receiving states (USA, France, Italy, Canada, Sweden, Switzerland and the Netherlands), and between 1993 and 1997 international adoptions increased from 16,027 to 23,199. This trend seems to be confirmed also by a more recent work (Selman 2006) based on the analysis of data from 20 receiving countries: results showed that inter-country adoption increased by 42% between 1998 and 2004.…”
Section: Incidence Of the Phenomenonsupporting
confidence: 83%
“…With respect to this trend, UNICEF (1999) has estimated the number of international adoptions to seven major receiving states (USA, France, Italy, Canada, Sweden, Switzerland and the Netherlands), and between 1993 and 1997 international adoptions increased from 16,027 to 23,199. This trend seems to be confirmed also by a more recent work (Selman 2006) based on the analysis of data from 20 receiving countries: results showed that inter-country adoption increased by 42% between 1998 and 2004.…”
Section: Incidence Of the Phenomenonsupporting
confidence: 83%
“…Ultimately, the pattern of intercountry adoption was called the ''quiet migration'' (Selman 2002) and in the year 2004 there were 45,000 children relocated from one country to another by means of intercountry adoption (Selman 2006). The practice has been in decline ever since (Selman 2009).…”
Section: Intercountry Adoption: a Controversial Interventionmentioning
confidence: 97%
“…En 2004, con 5.541 adopciones en el extranjero, España se convierte en el segundo país del mundo -después de EE. UU.-en adopciones internacionales (Selman, 2006(Selman, : 189, 2012 1 . El año 2004 supone un punto de inflexión en la tendencia del flujo de adopciones internacionales en España.…”
Section: El Baby Boom De Las Adopciones Internacionales En Españaunclassified